2021
DOI: 10.1038/s41598-020-80839-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intraocular pressure using systemic variables or fundus photography with deep learning in a health examination cohort

Abstract: The purpose of the current study was to predict intraocular pressure (IOP) using color fundus photography with a deep learning (DL) model, or, systemic variables with a multivariate linear regression model (MLM), along with least absolute shrinkage and selection operator regression (LASSO), support vector machine (SVM), and Random Forest: (RF). Training dataset included 3883 examinations from 3883 eyes of 1945 subjects and testing dataset 289 examinations from 289 eyes from 146 subjects. With the training data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…In our previous studies in general populations, an age-dependent decline of IOP was observed. (40,41) The balance between aqueous humor inflow and outflow determines the IOP. Aging causes decreased aqueous humor production (42) and increased trabecular meshwork resistance; (43) thus, SH might affect the IOP via the effects of age.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies in general populations, an age-dependent decline of IOP was observed. (40,41) The balance between aqueous humor inflow and outflow determines the IOP. Aging causes decreased aqueous humor production (42) and increased trabecular meshwork resistance; (43) thus, SH might affect the IOP via the effects of age.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed AUC from 0.89 to 0.97, according to different conditions [ 28 ]. Interestingly, performance of IOP prediction between a multivariate linear regression model (MLM) with 35 systemic variables and a DLS with colour fundus images showed that the former had a better predictive value [ 29 ]. The results may support that it may be better to use demographics to predict physiological parameters than to do glaucoma screening with images.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular pressure (IOP) is the amount of fluid pressure within the eye and is one of the most important examination metrics in ophthalmic clinics ( 11 ). It is an important marker for many ophthalmic diseases such as glaucoma and intraocular pressure that is too high or too low will damage eye tissues and visual functions to different degrees ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that according to a previous study, there was a significant increase in IOP in patients with severe and critical COVID-19 disease ( 15 ). Therefore, it is reasonable to think that in the autoimmune stage of COVID-19, a considerable number of patients may exhibit subclinical ocular inflammation and possibly high intraocular pressure ( 11 ). If high IOP is not dealt with in time, it may lead to irreversible vision loss.…”
Section: Introductionmentioning
confidence: 99%